THE CONTEXTUALIZATION OF DREAMS IN THE OLD TESTAMENT AND SOME SELECTED NEW RELIGIOUS MOVEMENTS, ILE-IFE - Abiola Ayodeji Olaniyi; David O. Olayiwola (European Scientific Journal, ESJ, 2014)
This paper addressed the contextualization of dream interpretation in the transformation of traditional African theories of origin of the universe and how the universe operated in Ile-Ife. It highlighted prominent demonstration of spiritual ability that abounded among members of the New Religious Movements (NRMs) at Ile-Ife. The NRMs were the Cherubim and Seraphim Unification Church of Nigeria (C&SUCN), the Church of the Lord Aladura (CLA) and Eckankar (Eck) at Ile-Ife. It employed biblical contextualization of ancient Near Eastern and Old Testament interpretation of dreams in exposing the theology of the NRMs that influenced moral change among the youths at Ile-Ife. It concluded with the recommendation that every idea of fatalism and predestination needed to be confronted with an ideology of a redeemable world by emphasizing virtues of discipline and submission to authority for maturity in interpersonal relations.